Estudo geofísico de vazamento de combustíveis em posto de abastecimento - Menezes, Aline Muriel; Moreira, César Augusto [UNESP]; Ilha, Lenon Melo; Schweig, Camila [UNESP] (My University, 2011)
The geoelectrical methods have been widely used in research involving the evaluation and monitoring of areas with environmental risk. This paper presents the results of applying the Electrical Resistivity method by electrical profiling technique to investigate the fuel presence in soil and groundwater proceeding in station gas, located in an urban area Caçapava do Sul (RS), on soil in situ, from modification of Caçapava granite. The results suggest an association between low resistivity anomalies zone with potentially degraded from underground tanks worthless on the form of free phase, now represented as residual phase. The results of the model inversion are consistent with the standards expected for hydrocarbons present in the saturated zone. The electrical resistivity method proved to be an important tool for assessment and environmental monitoring in conjunction with direct methods of investigation.

Os métodos geoelétricos têm sido amplamente utilizados em pesquisas que envolvam o processo de avaliação e monitoramento de áreas com risco ambiental. Este trabalho apresenta os resultados da aplicação do método da Eletrorresistividade, através da técnica de caminhamento elétrico para investigar a presença de combustíveis no solo e águas subterrâneas provenientes de um posto de combustíveis, localizado na zona urbana de Caçapava do Sul (RS), sobre solo in situ, produzido por alteração do granito Caçapava. Os resultados sugerem uma associação entre anomalias de baixa resistividade e zonas com combustível degradado proveniente de tanques enterrados inutilizados, sobre a forma de fase livre, atualmente representada como fase residual. Os resultados dos modelos de inversão são condizentes com os padrões esperados para hidrocarbonetos presente na zona saturada do perfil de alteração. O método da Eletrorresistividade demonstrou ser um instrumento importante para avaliação e monitoramento ambiental em conjunto com métodos diretos de investigação. Palavras-chave: combustíveis, NAPLs, eletrorresistividade, resistividade.
Geophysical study in seepage fuel in station gas
Keywords: Eletroresistivity; Fuel; NAPLs; Resistivity; electrical resistivity; environmental monitoring; environmental risk; gas; geoelectric field; geophysical method; granite; hydrocarbon; numerical model; phreatic zone; seepage; urban area; Brazil; Cacapava do Sul; Rio Grande do Sul